2007
DOI: 10.1021/es070664+
|View full text |Cite
|
Sign up to set email alerts
|

Recent Water Level Declines in the Lake Michigan−Huron System

Abstract: Great Lakes water levels have fluctuated over thousands of years. High water levels were a problem in the 1980s, but a recent sudden drop in Lakes Michigan and Huron has caused particular concern, in part because lower water levels are consistent with many global climate change scenarios. We examined water level data (1860-2006) representing Lakes Michigan and Huron to evaluate changes in both long-term and seasonal patterns over time, and explore relationships with candidate predictor variables. Our tools for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 32 publications
2
53
0
Order By: Relevance
“…As sensitive and good indicators of changing environments at both regional and global scales [3][4][5][6][7], lakes have long been an academic focus. The variations in lake area and lake water levels and the responses to climate change and intensifying anthropogenic activities have been widely investigated all over the world in recent years [8][9][10][11][12][13]. For lakes widely distributed across ungauged basins (i.e., those lacking meteorological and hydrological stations) and in remote and poor regions, it is very difficult to quantify lake dynamics and the causes of variations.…”
Section: Introductionmentioning
confidence: 99%
“…As sensitive and good indicators of changing environments at both regional and global scales [3][4][5][6][7], lakes have long been an academic focus. The variations in lake area and lake water levels and the responses to climate change and intensifying anthropogenic activities have been widely investigated all over the world in recent years [8][9][10][11][12][13]. For lakes widely distributed across ungauged basins (i.e., those lacking meteorological and hydrological stations) and in remote and poor regions, it is very difficult to quantify lake dynamics and the causes of variations.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, some authors have found recent significant positive trends in evaporation [52,53], and although variability associated with evaporation has historically been too small to significantly affect the lake levels, a persistent positive decadal-scale evaporation anomaly is now resulting in significant cumulative lake-level changes [8]. As discussed in Section 2.1, the precipitation-driven lake-level components have explained a majority of the historic lake-level behavior; however, their time series are beginning to diverge, stemming from increasing evaporative losses over the past couple of decades.…”
Section: Discussionmentioning
confidence: 99%
“…The method is an iterative nonparametric procedure using repeated loess fitting (Sellinger et al 2007). A time series of monthly monitoring data may be considered a sum of three components: high-frequency seasonal, low-frequency, long-term (or trend), residual (variation not explained by time).…”
Section: Methodsmentioning
confidence: 99%
“…Such variability results from the customary seasonal oscillation and from the superimposed effect of several nonseasonal forcing factors. Variation of the seasonal cycle has been studied using seasonal-trend decomposition using loess (local error sum of squares) (STL) method for water level (Lenters 2001;Sellinger et al 2007) and nutrient trend (Qian et al 2000;Wang et al 2012b). In this case, the trend of water level fluctuations in Lake Baiyangdian can be decomposed to depict intra-annual water level variation, using STL method.…”
Section: Introductionmentioning
confidence: 99%